Endocrine Complications of Cystic Fibrosis: A Multisystem Disease of the Endocrine Organs - Ode, Katie Larson; Chan, Christine L.; Granandos, Andrea; Putman, Melissa; Moheet, Amir (Seminars in Respiratory and Critical Care Medicine, 2019)
Cystic fibrosis (CF) is one of the most common life-limiting genetic disorders. Although CF is typically considered primarily as a pulmonary disease, the CF conductance transmembrane regulator is present throughout the body. From an endocrine perspective, this multisystem disease manifests primarily in the pancreas as a unique form of diabetes (CF-related diabetes mellitus), as bone disease, and as reproductive health issues in people with CF. These complications have become ever more concerning to people with CF as treatment for pulmonary disease improves and lifespans lengthen, increasing the impact of nonpulmonary complications. Our understanding of the management of these concerns continues to evolve, and, although there are some effective treatments, there is great opportunity for continued investigation into the pathophysiology of the endocrine complications of CF and their treatment.
Keywords: cystic fibrosis-related diabetes; cystic fibrosis; insulin; cystic fibrosis bone disease; hypogonadism; infertility; continuous glucose monitoring; bone mineral density